The Israeli-Palestinian conflict - Lüsted, Marcia Amidon (Special reports (Essential Library (Firm)), 2018)
Examines the origins of the Israeli-Palestinian conflict, where the situation is today, and what is being done to resolve issues between the two parties. Includes full-color photographs, essential facts, source notes, a glossary, resources for further learning, and an index.